Pemberdayaan Kader Dalam Deteksi dan Reduksi Kecemasan Ibu Hamil - Aisyah, Risqi Dewi; Prafitri, Lia Dwi (Journal of Community Development, 2024)
Perinatal anxiety affects about 17% of women; While up to 84% of women experience perinatal stress. Other scientific studies have shown that anxiety during pregnancy is linked to an increased risk of pregnancy complications, such as premature birth, low birth weight, as well as mental health problems in children, such as anxiety and depression. Empowering health cadres in the community can be an effective strategy to reduce the anxiety level of pregnant women. The purpose of dedication is to provide support to partners in efforts to reduce anxiety for pregnant women by empowering NA cadres who are responsive to women's health. The methods carried out are Forum Discussion Group (FGD), Education, empowerment practices, monitoring and evaluation, and follow-up plans. The dedication carried out was able to increase the knowledge of NA cadres including psychological adaptation, anxiety of pregnant women and husband support, this was seen from the increase in mean value, showing an increase in cadre knowledge from less to good from the material provided starting from an increase in knowledge of psychological adaptation of good knowledge by 28.6% (From good knowledge 57.1% to 85.7%, anxiety of pregnant women good knowledge increased by 28%,  Husband support was good at 39.3% (From good knowledge 46.4% to 85.7%). The expected follow-up is to increase responsive cadres in women's health, especially pregnant women and provide social support to reduce the health of pregnant women.